Observations from Three Suicide Cases Post-Yogyakarta Earthquake, 2006 - Carla R Marchira (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Saturday, May 27th 2006, 05:53AM, a 5.9 Richter's Scale tectonic earthquake shook the Province of Yogyakarta. Mass panic swept the city due to a spreading rumor of an oncoming tsunami wave which is to follow the earthquake. Traffic all over the city was jammed, buildings collapsed, and many were injured and killed by the rubble. Due to the shock of the situation, the trauma resulted in mental distress for many of those directly and indirectly affected.Objective: To report the suicide cases following the earthquake in five districts of Yogyakarta Province.Method: To do in-depth interviews with the families of the suicide victims to describe suicide cases shortly after the Yogyakarta earthquake.Result: There were three consecutive suicide cases shortly after the earthquake (2-6 days). Two cases come from the most affected area, Bantul District and one case comes from the dry area, Gunungkidul District.Conclusions:There were three consecutive suicide cases shortly after the earthquake (1st week), all cases were males. There was no evidence that the earthquake caused the suicide of these cases directly, but the impact of the earthquake may have increased stress and inability to cope that ultimately led to their tragic ends.Keywords: mental health, trauma, Yogyakarta Earthquake, suicide